Evaluation of Artificial Intelligence Significance for ERP and Production Automation: Integrating Artificial Intelligence and SCM to Optimize ERP Production Life Cycle (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this powerful period of globalization, success of organizations is usually getting more and more difficult. Clients demand for wide range, high quality, better support, better dependability, faster delivery, and extremely personalized products. Hence, extreme competition happens between businesses, which effects on the life period of items, because well as on rate, quality and costs. Therefore, versatility when it comes to acceleration, price and quality requirements to happen for an business to achieve a competitive advantage. As a trimming age group situation, automation is usually constructed on the pillars of Artificial Intelligence (AI). This paper concentrates on require of AI and SCM with each other to make ERP production life cycle more effective and efficient.